The effect of endocannabinoid system on energy metabolism and obesity [Endokanabi̇ni̇d si̇stemi̇n, enerji̇ metaboli̇zmasi ve obezi̇teye etki̇si̇] - (:unkn) unknown (My University, 2007)
Recently, it has been defined that Marijuana and its major psychotropic component Δ9-tetrahydrocannabinol, CB1 cannabinoid receptors and endocannabinoids which include endogenous ligands stimulate appetite and increase body weight by controlling energy balance. It has been shown in the animal experiments and human clinical studies that the endocannabinoid system controls food intake by central and peripheral mechanism and stimulates lipogenesis and fat accumulation. The formation of endocannabinoid system and its receptors, ligands and energy metabolism of this physiological system and its effect on energy metabolism have been discussed.
Keywords: Endocannabinoid system; Energy balance; Marijuana; Obesity